Questions of Research of Digitalization in Various Fields of Activity - N. O. Yakushev (Цифровая трансформация)
The ability to implement strategic priorities of digital development and intensify the activities of various stakeholders (government, science, business, enterprises) in high-tech sectors are necessary conditions for the successful development of the country and solving economic problems. A key affiliation related to digitalization issues has been highlighted. Based on the analysis of scientific literature, those accents (availability of digital technologies, impact on managerial and institutional spheres, sectoral and territorial features, applied significance) on which researchers focus their attention, are identified. The directions are systematized depending on the digitalization of individual objects, including the necessary elements of digitalization.